1992
DOI: 10.1148/radiology.184.1.1609107
|View full text |Cite
|
Sign up to set email alerts
|

Renal colic: diagnosis and outcome.

Abstract: To assess whether ultrasonography (US) with or without plain abdominal radiography (kidney, ureter, bladder [KUB] radiography) can replace intravenous urography (IVU) in detection of acute urinary tract obstruction, 101 consecutive patients with renal colic were evaluated with US followed immediately by IVU. Receiver operating characteristic (ROC) curves for US diagnosis of acute urinary tract obstruction yielded sensitivities of 91% and 92% for two reviewers at a specificity of 90%. There was no statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 0 publications
0
38
1
3
Order By: Relevance
“…Eighteen were admitted from the ED for an intervention, and 32 had their intervention after being discharged from the ED. The urological interventions performed on these patients included ESWL (12 patients), ureteroscopy (27), percutaneous nephrostomy (10), open surgery (1), or more than one procedure (7). In reviewing the operative reports of the patients who underwent an intervention, the reasons cited by the urologists in the charts for performing a procedure on the urinary calculi included: calculus size (32%), development of an infected calculus (19%), severe obstruction (19), location of calculus in the upper ureter (14%), acute renal failure (10%) and persistent pain (6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen were admitted from the ED for an intervention, and 32 had their intervention after being discharged from the ED. The urological interventions performed on these patients included ESWL (12 patients), ureteroscopy (27), percutaneous nephrostomy (10), open surgery (1), or more than one procedure (7). In reviewing the operative reports of the patients who underwent an intervention, the reasons cited by the urologists in the charts for performing a procedure on the urinary calculi included: calculus size (32%), development of an infected calculus (19%), severe obstruction (19), location of calculus in the upper ureter (14%), acute renal failure (10%) and persistent pain (6%).…”
Section: Resultsmentioning
confidence: 99%
“…8,15,[19][20][21][22][23] Our predictive variables for intervention are remarkably similar to other studies 8,12,15,[23][24][25] and demonstrate that our sample of renal colic patients is comparable to other populations described in the literature. 14,[26][27][28] Although not all patients had an intervention or were enrolled in the study, we Not enrolled in study n = 81…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Thus, unenhanced helical CT is currently the imaging test of choice for evaluating patients with acute fl ank pain for whom the clinical diagnosis is uncertain. [22][23][24][25][26][27][28][29] In the CT evaluation of ureteral calculi, the agreement between the group of senior residents and the consensus among the abdominal radiologists were very good, as shown in Table 3. The interobserver agreement for identifying the ureteral stone was almost perfect (k = 0.81).…”
Section: Ureterovesical 47%mentioning
confidence: 92%
“…In a study by Haddad et al [8], the clinical diagnosis was accurate in only 70 of 101 patients in whom the kidney problem was the cause of pain. Mutagi et al [9]reported that the sensitivity and specificity of a clinical scoring system based on signs and symptoms was 73 and 46%, respectively, in 85 patients with suspected renal colic.…”
Section: Diagnosismentioning
confidence: 99%
“…The sensitivity of KUB in detecting ureteral calculi ranges from 45 to 59%, thus providing limited value in the diagnosis of ureteral stones [8, 9, 11]. Superimposed bowel and bone obscure some calculi, and vascular calcifications, especially pelvic phleboliths, may be confused with stones.…”
Section: Diagnosismentioning
confidence: 99%